Between State Duty and Peace Mission: The Other Side & Experience of Indonesia Peacekeeping Force in the Middle East - Itawan, Devi; Saumia, Zulfa; Hudaya, Padhil; Saputra Adiguna, Richad; Lestari, Inda (Siginjai: Jurnal Sejarah, 2024)
Further research has been conducted on the role of the Indonesian National Army and the Indonesian laskar after the declaration of independence on 17 August 1945 and during the revolutionary period from 1945 to 1949. However, after decolonization in the 1950s, military history including the lives of its members and their personal lives received less space in the narrative of military history. Peace veteran is a title given specifically to young Indonesians who had participated as special forces under the auspices of the United Nations. These young men did not only come from the TNI but also from student regiments who had the opportunity to join this special peacekeeping force. The main focus of this article revolves around their efforts to guard the border between Egypt and ‘Israel’ during the war in the Middle East. This article will use oral sources and personal documents from various Indonesian peacekeeping forces who served during this period. The results of the study show that although they were faced with uncertain situations, far from their families, and preparing to face the enemy, there was another side to their experiences, namely, meeting colleagues from other countries, language gaps, and other “normal” activities that they were still able to carry out while on duty.